MINANGKABAU LOCALITY SATIRE IN PROSE HUMOR MINANGKABAU LANGUANGE BY HERU JONI PUTRA: SATIR LOKALITAS MINANGKABAU DALAM PROSA HUMOR BERBAHASA MINANGKABAU KARYA HERU JONI PUTRA - Rio Rinaldi; Romi Isnanda; Ineng Naini (Jurnal Kata, 2021)
This paper aims to describe locality satire of Minangkabau in the humorous prose of Minangkabau language by Heru Joni Putra. This research is descriptive qualitative with data in the form of words that can be formulated as locality satire of Minangkabau. This study uses an anthropological approach to explain the language, society, and culture that is told in the story. Based on the results of data identification, the locality satire of Minangkabau in Minangkabau prose by Heru Joni Putra is a critical attitude towards human behavior, political systems, culture, and so on, which is mediated by language. The criticism of these weaknesses is stated in order to remind those who are criticized to make improvements ethically and aesthetically to the things intended by the author. Wise readers will assume that literary works, including HJP's Minang humorous prose, are fictitious stories that basically do not contain only realist content. Through a pralogical and satirical way of expressing, the author as a creator has the right to convey his ideas through the creative process he does, as well as the function of journalists when writing essays, articles, or the like.